(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
What are the motivations that support Ukrainians’ strenuous and unexpected resistance to the invasion, which began in 2014, of their republic? For many political observers, journalists, researchers and scholars, the Ukrainians’ tenacity, courage, and determination remain little or not fully understandable to this day. In reality, the reasons for that tenacity are many. However, the main has been and continues to be the opportunity, in the thirty years of Independence, to discover one’s own history, both from the period of the Russian and the Soviet Empires. Ukraine’s history has been difficult, punctuated with long denied, counterfeited, and obscured tragedies. Its discovery is the most important reason that supports the will to resist today. What is taking place today thus is the intensification of a centuries-long process of de-colonization that not only affects the ethnic Ukrainian component, but also becomes an attempt to block the way for the return of autocratic and totalitarian rule that threatens to overwhelm a fragile civic nation in the making for the past 30 years.